Analisis Kinerja Pegawai Bagian Pelayanan Di PT. Pos Indonesia (Persero) Kantor Pos Subang - Engkus Engkus; Nadiya Ulfah (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2019)
The research focused on the performance of employees in the service section. The main problem in this study is that there are still employees who do not respond to the procedures set at the Subang Post Office. The purpose of this study is to analyze how the performance of employees in the service sector. The research method used in this study is a qualitative approach with descriptive method. Data collection techniques used in the form of observation techniques, interviews, and literature. The results showed that the quantity of work done by employees in doing work not in accordance with the predetermined target, the quality of work results of employees at the Subang Post Office could not be said to be good, the time period that can be achieved in doing work is quite fast and quite good, in terms of attendance it is still not good because there are still late employees in doing work, and the ability to work with the leaders or fellow employees that has been established is good. And the conclusions of this study are that the employees in the Subang Post Office service are not optimal.Keywords: Public Service, Employee Performance, Leadership, Human Resource Development